Patterns of international governance in the Arctic and China’s approach - Long, Zhao (Polar Research Institute of China - PRIC, 2016)
The process of rapid change in the Arctic is creating both opportunities and challenges. This paper highlights interactions between different actors in the Arctic in response to multidimensional environmental, political, commercial, and human challenges. It shows that international governance in the Arctic can be characterized by global, multilateral, and regional patterns derived from different mechanisms such as the Arctic Council or the Ilulissat declaration platform, and these interactions are based on common acknowledgment of challenges, mutual interests, and coordinated actions. The paper also examines China’s participation in international governance in the Arctic. Distinguish from non-Arctic states in a general sense, China as an important stakeholder has both the rights and the capacity to be engaged in multilevel governance patterns. The substantive contribution of China’s participation an explorer in scientific cooperation, a pioneer promoting environmental protection, a potential consumer and investor in relation to economic opportunities, and a promoter of local development are deeply interdepended with the future of development of three governance patterns relating to international governance in the Arctic.